SUSCEPTIBILITY -WEIGHTED IMAGING FOR DETECTION OF THROMBUS IN CEREBRAL VASCULATURE - Santosh Kumar Padhy; Rajesh Pattanaik; Ashis Kumar Satapathy (Student's Journal of Health Research, 2023)
Background & Objectives: Cerebral vascular thrombosis can lead to devastating disability if not timely diagnosed and treated. Susceptibility-weighted imaging (SWI) is evolving as means of rapid investigation in the detection of intravascular clots in vascular thrombosis. The aim of this study is to detect the diagnostic accuracy of SWI and its role in cerebral vascular thrombosis. Materials & Methods: The study was done on 40 patients, who underwent MR imaging of the brain using GЕ Optima MR 360 1.5 Tеslа MRI machine at the Department of Radiodiagnosis of IMS & SUM Hospital, Bhubaneswar. The data collected were categorized as arterial or venous infarcts, which were further evaluated on the basis of the presence of intravascular clot, venous congestion, hemorrhagic areas, zone of penumbra, and risk of hemorrhagic transformation on SWI with conventional MR sequences and NC-MRA/MRV. Results: In this study, SWI showed a sensitivity of 88.24% in the detection of intravascular thrombus as compared to 60.00% on combined T1W and T2W images with a p-value of 0.004. SWI has a sensitivity of 85.71% as compared to 72% on NC-MRA/MRV for intravascular clot detection with a p-value of 0.001. It could also detect the presence of hemorrhagic areas and cortical venous congestion with 100% sensitivity as compared to other sequences. In cerebral ischemic stroke, it could additionally detect the zone of penumbra and risk of hemorrhagic transformation which could not be detected on other sequences. Conclusion: SWI is considered a useful sequence that detects the presence of intravascular thrombus due to an increased concentration of deoxyhemoglobin. It also provides useful additional information regarding the presence of hemorrhagic areas and their risk of occurrence following thrombolytic therapy. Hence, SWI should be included in routine imaging protocol of the brain.